Early cardio-oncology intervention in thoracic radiotherapy: prospective single-arm pilot study - Samuel C. Zhang; Jordan O. Gasho; Celeste Eno; Katrina D. Silos; Felicity Pendergast; Wenjuan Zhang; Eric Vail; Mitchell Kamrava; Behrooz Hakimian; Amin Mirhadi; Raymond H. Mak; Andriana P. Nikolova; et al. (Communications Medicine)
Abstract Background While there is increasing recognition of the morbidity of cardiovascular disease in cancer survivors, including accelerated atherosclerosis following thoracic radiotherapy, patients are frequently under-optimized for cardiovascular risk. Methods In this prospective single-arm cohort pilot study, patients were treated with high-dose thoracic radiotherapy and had early consultation with cardio-oncology. Twenty patients were enrolled. The primary endpoint was adherence to cardio-oncology consultation. Secondary endpoints were cardiovascular medication intervention rate and patient-reported intervention perspectives. Clonal hematopoiesis of indeterminate potential, a major cardiovascular risk marker enriched in patients with cancer and induced by radiation exposure, was measured as an exploratory endpoint. Results The cohort median age is 71 years. Most patients are female (13/20), have primary lung or esophageal carcinoma (16/20), and 7/20 have pre-existing cardiovascular disease. We show that cardio-oncology consultation adherence is high (19/20) and results in cardiovascular medication optimization changes in most patients (12/19), most commonly to initiate or intensify statin therapy (8/12). 8/12 patients with a primary cardiologist prior to enrollment have medication changes recommended. Most (12/17) participants are glad to learn about their heart health during cancer treatment. Clonal hematopoiesis is detectable prior to treatment in 8/20 patients and three develop new variants after treatment (1/3 de novo). Conclusions We observe that early cardio-oncology consultation is feasible, leads to cardiovascular medication optimization in the majority (>60%) of participants, most commonly to initiate or intensify statin therapy. New clonal hematopoiesis variants are detectable early after radiotherapy and the impact on post-treatment cardiovascular risk is worthy of further study.